PIC16F1847 microcontroller-based programmable logic controller : intermediate concepts - Uzam, Murat, 1968- (Boca Raton, FL : CRC Press, 2021)
The volume focusses on intermediate concepts of the PIC16F1847-Based PLC project, and covers arithmetical operation ability of PLCs, logical function performers and operations like AND, NAND, OR, NOR. Further, it explains shift and rotate macros moving bits in a register to right or left, and selection macros enabling one value to be selected from several given values according to certain criteria. Demultiplexer circuit is illustrated, which is used to send a signal to one of many devices. Finally, it explains decoder, priority encoder and conversion macros. All the concepts are supported using flowcharts. Aimed at researchers and graduate students in electrical engineering, power electronics, robotics and automation, sensors, this book: Presents arithmetical and logical macros to carry out arithmetical and logical operations to be used for 8-bit or 16-bit variables and/or constant values. Provides shift and rotate macros to do arithmetical or logical shift and rotate operations to be used for 8-bit or 16-bit variables. Proposes selection macros to enable the user to do 8-bit or 16-bit move, load, selection, maximum, minimum, limiting, multiplexing and byte multiplexing operations. Develops demultiplexer macros, decoder macros and priority encoder macros to be used as combinational circuits. Presents conversion macros to provide functions to convert given data from one format to another one.
Chapter 1 -- Arithmetical Macros 1.1 Macro "R1addR2" 1.2 Macro "R1addR2-16" 1.3 Macro "RaddK" 1.4 Macro "RaddK-16" 1.5 Macro "R1subR2" 1.6 Macro "R1subR2-16" 1.7 Macro "RsubK" 1.1 Macro "RsubK-16" 1.9 Macro "R1mulR2" 1.10 Macro "DivU16by8" 1.11 Macro "incR" 1.12 Macro "incR-16" 1.13 Macro "decR" 1.14 Macro "decR-16" 1.15 Macro "Hbit-CNT" (High Bit Counter) 1.16 Macro "Lbit-CNT" (Low Bit Counter) 1.17 Examples for Arithmetical Macros Chapter 2 -- Logical Macros 2.1 Macro "R1andR2" 2.2 Macro "RandK" 2.3 Macro "R1nandR2" 2.4 Macro "RnandK" 2.5 Macro "R1orR2" 2.6 Macro "RorK" 2.7 Macro "R1norR2" 2.8 Macro "RnorK" 2.9 Macro "R1xorR2" 2.10 Macro "RxorK" 2.11 Macro "R1xnorR2" 2.12 Macro "RxnorK" 2.13 Macro "invR" 2.14 An Example for Logical Macros Chapter 3 -- Shift and Rotate Macros 3.1 Macro "Ashift-R" (Arithmetic Shift Right Rin) 3.2 Macro "Ashift-R-16" (Arithmetic Shift Right Rin) 3.3 Macro "Lshift-R" (Logical Shift Right Rin) 3.4 Macro "Lshift-R-16" (Logical Shift Right Rin) 3.5 Macro "Lshift-L" (Logical Shift Left Rin) 3.6 Macro "Lshift-L-16" (Logical Shift Left Rin) 3.7 Macro "shift-R" (Shift Right Rin) 3.8 Macro "shift-R-16" (Shift Right Rin) 3.9 Macro "shift-L" (Shift Left Rin) 3.10 Macro "shift-L-16" (Shift Left Rin) 3.11 Macro "rotate-R" (Rotate Right Rin) 3.12 Macro "rotate-R-16" (Rotate Right Rin) 3.13 Macro "rotate-L" (Rotate Left Rin) 3.14 Macro "rotate-L-16" (Rotate Left Rin) 3.15 Macro "Swap" (Swap Rin) 3.16 Examples for Shift and Rotate Macros Chapter 4 -- Selection Macros 4.1 Macro "move-R" (Move) 4.2 Macro "load-R" (Load) 4.3 Macro "select" (Selection of One of Two 8-Bit Input Variables) 4.4 Macro "select-16" (Selection of One of Two 16-Bit Input Variables) 4.5 Macro "max-5" (Maximum in Five 8-Bit Variables) 4.6 Macro "max-10" (Maximum in Ten 8-Bit Variables) 4.7 Macro "max- N80" (Maximum in N 8-Bit Variables, N = 2, 3, ..., 80) 4.8 Macro "max- N40-16" (Maximum in N 16-Bit Variables, N = 2, 3, ..., 40) 4.9 Macro "max- N255" (Maximum in N 8-Bit Variables, N = 2, 3, ..., 255) 4.10 Macro "max- N255-16" (Maximum in N 16-Bit Variables, N = 2, 3, ..., 255) 4.11 Macro "min-5" (Minimum in Five 8-Bit Variables) 4.12 Macro "min-10" (Minimum in Ten 8-Bit Variables) 4.13 Macro "min- N80" (Minimum in N 8-Bit Variables, N = 2, 3, ..., 80) 4.14 Macro "min- N40-16" (Minimum in N 16-Bit Variables, N = 2, 3, ..., 40) 4.15 Macro "min- N255" (Minimum in N 8-Bit Variables, N = 2, 3, ..., 255) 4.16 Macro "min- N255-16" (Minimum in N 16-Bit Variables, N = 2, 3, ..., 255) 4.17 Macro "limiter" 4.18 Macro "limiter-16" 4.19 Multiplexer Macros 4.20 Macro "mux-2-1" (2#xF0B4;1 MUX) 4.21 Macro "mux-2-1-E" (2#xF0B4;1 MUX with Enable Input) 4.22 Macro "mux-4-1" (4#xF0B4;1 MUX) 4.23 Macro "mux-4-1-E" (4#xF0B4;1 MUX with Enable Input) 4.24 Macro "mux-8-1" (8#xF0B4;1 MUX) 4.25 Macro "mux-8-1-E" (8#xF0B4;1 MUX with Enable Input) 4.26 Macro "mux-16-1" (16#xF0B4;1 MUX) 4.27 Macro "mux-16-1-E" (16#xF0B4;1 MUX with Enable Input) 4.28 Macro "B-mux-2-1-E" (2#xF0B4;1 Byte Multiplexer with Enable Input) 4.29 Macro "B-mux-4-1-E" (4#xF0B4;1 Byte Multiplexer with Enable Input) 4.30 Macro "B-mux-8-1-E" (8#xF0B4;1 Byte Multiplexer with Enable Input) 4.31 Examples for Selection Macros Chapter 5 -- Demultiplexer Macros 5.1 Macro "Dmux-1-2" (1#xF0B4;2 DMUX) 5.2 Macro "Dmux-1-2-E" (1#xF0B4;2 DMUX with Enable Input) 5.3 Macro "Dmux-1-4" (1#xF0B4;4 DMUX) 5.4 Macro "Dmux-1-4-E" (1#xF0B4;4 DMUX with Enable Input) 5.5 Macro "Dmux-1-8" (1#xF0B4;8 DMUX) 5.6 Macro "Dmux-1-8-E" (1#xF0B4;8 DMUX with Enable Input) 5.7 Macro "Dmux-1-16" (1#xF0B4;16 DMUX) 5.8 Macro "Dmux-1-16-E" (1#xF0B4;16 DMUX with Enable Input) 5.9 Macro "B-Dmux-1-2-E" (1#xF0B4;2 Byte DeMultiplexer with Enable Input) 5.10 Macro "B-Dmux-1-4-E" (1#xF0B4;4 Byte DeMultiplexer with Enable Input) 5.11 Macro "B-Dmux-1-8-E" (1#xF0B4;8 Byte DeMultiplexer with Enable Input) 5.12 Macro "Dispatcher-1-8-E" (1#xF0B4;8 Dispatcher with Enable Input) 5.13 Macro "Patcher-8-1-E" (8#xF0B4;1 Patcher with Enable Input) 5.14 Examples for Demultiplexer Macros Chapter 6 -- Decoder Macros (Available as E-Ancillaries) 6.1 Macro "decod-1-2" (1#xF0B4;2 Decoder with Active High Outputs) 6.2 Macro "decod-1-2-AL" (1#xF0B4;2 Decoder with Active Low Outputs) 6.3 Macro "decod-1-2-E" (1#xF0B4;2 Decoder with Active High Outputs and with Active High Enable Input) 6.4 Macro "decod-1-2-E-AL" (1#xF0B4;2 Decoder with Active Low Outputs and with Active High Enable Input) 6.5 Macro "decod-2-4" (2#xF0B4;4 Decoder with Active High Outputs) 6.6 Macro "decod-2-4-AL" (2#xF0B4;4 Decoder with Active Low Outputs) 6.7 Macro "decod-2-4-E" (2#xF0B4;4 Decoder with Active High Outputs and with Active High Enable Input) 6.8 Macro "decod-2-4-E-AL" (2#xF0B4;4 Decoder with Active Low Outputs and with Active High Enable Input) 6.9 Macro "decod-3-8" (3#xF0B4;8 Decoder with Active High Outputs) 6.10 Macro "decod-3-8-AL" (3#xF0B4;8 Decoder with Active Low Outputs) 6.11 Macro "decod-3-8-E" (3#xF0B4;8 Decoder with Active High Outputs and with Active High Enable Input) 6.12 Macro "decod-3-8-E-AL" (3#xF0B4;8 Decoder with Active Low Outputs and with Active High Enable Input) 6.13 Macro "decod-4-16" (4#xF0B4;16 Decoder with Active High Outputs) 6.14 Macro "decod-4-16-AL" (4#xF0B4;16 Decoder with Active Low Outputs) 6.15 Macro "decod-4-16-E" (4#xF0B4;16 Decoder with Active High Outputs and with Active High Enable Input) 6.16 Macro "decod-4-16-E-AL" (4#xF0B4;16 Decoder with Active Low Outputs and with Active High Enable Input) 6.17 Examples for Decoder Macros Chapter 7 -- Priority Encoder Macros (Available as E-Ancillaries) 7.1 Macro "encod-4-2-p" (4#xF0B4;2 Priority Encoder with Active High Outputs) 7.2 Macro "encod-4-2-p-E" (4#xF0B4;2 Priority Encoder with Active High Outputs and with Active High Enable Input) 7.3 Macro "encod-8-3-p" (8#xF0B4;3 Priority Encoder with Active High Outputs) 7.4 Macro "encod-8-3-p-E" (8#xF0B4;3 Priority Encoder with Active High Outputs and with Active High Enable Input) 7.5 Macro "encod-dec-bcd-p" (Decimal to BCD Priority Encoder with Active High Outputs) 7.6 Macro "encod-dec-bcd-p-E" (Decimal to BCD Priority Encoder with Active High Outputs and with Active High Enable Input Input) 7.7 Macro "encod-16-4-p" (16#xF0B4;4 Priority Encoder with Active High Outputs) 7.8 Macro "encod-16-4-p-E" (16#xF0B4;4 Priority Encoder with Active High Outputs and with Active High Enable Input) 7.9 Examples for Priority Encoder Macros Chapter 8 -- Conversion Macros 8.1 Macro "Conv-UsInt-2-BCD-U" (Unsigned Short Integer to Unpacked BCD Conversion) 8.2 Macro "Conv-UsInt-2-BCD-P" (Unsigned Short Integer to Packed BCD Conversion) 8.3 Macro "Conv-UInt-2-BCD-U" (Un
OCLC-licensed vendor bibliographic record.
Keywords: PIC microcontrollers; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Electronics / Circuits / General